2014
DOI: 10.1080/00222895.2014.912197
|View full text |Cite
|
Sign up to set email alerts
|

Verbal-Motor Attention-Focusing Instructions Influence Kinematics and Performance on a Golf-Putting Task

Abstract: The authors examined how varying the content of verbal-motor instructions and requesting an internal versus external focus influenced the kinematics and outcome of a golf putting task. On Day 1, 30 novices performed 120 trials with the instruction to focus attention either on performing a pendulum-like movement (internal) or on the desired ball path (external). After 20 retention trials on Day 2, they performed 20 transfer trials with the opposite instruction. Group differences for retention and a group by blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 46 publications
(51 reference statements)
1
7
0
1
Order By: Relevance
“…This was done by comparing their skill levels as defined in the 25 articles used for the study. Therefore, these findings will help promote the understanding of the development of skill required to achieve a certain kind of professionalism (Munzert et al, 2014). This is one of the first studies to analyse golf in terms of proficiency and the kinematics involved.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This was done by comparing their skill levels as defined in the 25 articles used for the study. Therefore, these findings will help promote the understanding of the development of skill required to achieve a certain kind of professionalism (Munzert et al, 2014). This is one of the first studies to analyse golf in terms of proficiency and the kinematics involved.…”
Section: Discussionmentioning
confidence: 80%
“…unclear Munzert, Maurer & Reiser (2014) This study examined how varying the content of verbal-motor instructions and requesting an internal versus external focus influenced the kinematics and outcome of a golf putting task.…”
Section: Synthesis Of Resultsmentioning
confidence: 99%
“…Several studies have reported more favorable motor learning via external focus than when internal focus or control conditions are used [11,12]. External focus improves putting accuracy, kinematic parameters [13], and muscle activity as measured by electromyography (EMG) [14], as it smooths the putting motion and decreases muscle activity in the lower extremities. Less muscle activity is required to complete efficient movements.…”
Section: Attention Focus During Balance Control and Sports Activitiesmentioning
confidence: 99%
“…An example of implicit instruction would be to mention “imagine kicking a ball”, “to facilitate extension of the knee. ” 11 Explicit instruction is the process whereby participant’s attention is consciously directed toward an internal focus (participant’s own movement patterns); for example, stating to “ keep the knees over the toes” 11 Previous research suggests that implicit and explicit feedback could influence both immediate outcome and short-term changes in motor learning (Munzert et al 2014 ; Pascua et al 2014 ). Most neuromuscular ACL injury prevention programs contain explicit instructions for performing correct movement patterns while landing (e.g., position of trunk, hips, knees, and feet) (Noyes et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%